Character Formation in Children through Periodic Counseling during the Covid-19 Period - Nurpita Sari; Imam Tabroni (Jurnal Pengabdian Masyarakat Bestari, 2022)
Today the development of science is rapid, starting from innovation and its efficient use so as to facilitate human tasks and work. This also has an impact on the field of education, because of the proliferation of mass media, especially electronic media of electronic, and the addition of the Youtube Application that makes it easier for students to get information on learning teaching materials. Not only that, the distribution of the internet and the telephon network that continues to be promoted has caused Indonesia to gradually continue to distribute innovations and developments in science and technology, where technology is now a very important necessity in people’s lives and in supporting both the education aspect. Often students access Youtube which is usefull wisely, for example to looking for teaching of materials, but is instead used to access pornographic videos, even videos of online games where the content contains bad language that which is more easily to absorbed by students. The purpose of this research was to determine the formation of character through regular counselling. This research method use is descriptive approach research method. Based of the action taken, this good behaviour counselling becomes an effective alternative behaviour to shape good in students, plus there are coaching methods and communication patterns that are always well maintained between educators, researchs, and students.